Hidden figures : (Harper, an imprint of HarperCollinsPublishers, 2018)
Based on the New York Times bestselling book and the Academy Award–nominated movie, author Margot Lee Shetterly and Coretta Scott King Illustrator Honor Award winner Laura Freeman bring the incredibly inspiring true story of four black women who helped NASA launch men into space to picture book readers!